Unravelling the Potential of Wild Endemic Sumatran Turmeric (Curcuma sumatrana Miq.) as a Candidate of Herbal Medicine for Neurodegenerative Diseases - Putra Santoso; Syafruddin Ilyas; Rita Maliza; Indah Fajarwati; Rauza Sukma Rita; Aldi Tamara Rahman; Jihan Aprilia Nawawi; Ivan Petrovsky; Muhammad Samudra Ilham; Ananda Fitriana (Science and Technology Indonesia, 2026)
Neurodegenerative diseases pose significant health challenges, while synthetic drugs are often associated with detrimental side effects. Hence, the search for herbal medicines is warranted. Curcuma sumatrana is traditionally used by Minangkabau people as a herbal medicine, but it remains scientifically underexplored. This study aims to evaluate its neuroprotective potential through phytochemical profiling, computational analyses, and biological assays. LC-MS/MS-QTOF profiling identified 13 compounds in the rhizome extract, predominantly terpenoids. In silico analyses predicted antioxidant, anti-inflammatory, and antineurodegenerative activities, while drug-likeness assessment suggested favorable bioavailability for all identified compounds. Furthermore, molecular docking targeting neurodegeneration-associated proteins revealed strong interactions of compounds namely brefeldin A, nigakilactone K, genistein, and 8-epi-loganic acid-6’-O-β-D-glucoside with MAPK1, TNF-α, BACE1, and CASP3, respectively. In addition, the extract exhibited notable antioxidant activity in the DPPH assay and ameliorated monosodium glutamate-induced cognitive impairment, hippocampal neurodegeneration, and elevated brain malondialdehyde levels in mice. Hence, C. sumatrana is a promising herbal medicine for neurodegenerative diseases, plausibly acting through the modulation of neurodegeneration-related pathways and antioxidant mechanisms. These findings provide a foundation for future drug discovery by identifying bioactive compounds with potential applications in the management of neurodegenerative disorders.